Can label or protein deuteration extend the phase relaxation time of Gd(III) spin labels? - E. Edinach; X. Zhang; C.-Y. Cui; Y. Yang; G. Mitrikas; A. Bogdanov; X.-C. Su; D. Goldfarb (Magnetic Resonance)
Pulse-dipolar electron paramagnetic resonance (PD-EPR) has emerged as an effective tool in structural biology, enabling distance measurements between spin labels attached to biomolecules. The sensitivity and accessible distance range of these measurements are governed by the phase memory time (Tm) of the spin labels. Understanding the decoherence mechanisms affecting Tm is crucial for optimizing sample preparation and spin-label design. This study investigates the phase relaxation behavior of two Gd(III) spin-label complexes, Gd-PyMTA and Gd-TPMTA, with various degrees of deuteration. These two complexes have significantly different zero-field-splitting (ZFS) parameters. Hahn echo decay and dynamical decoupling (DD) measurements were performed at W-band (95 GHz) in deuterated solvents (D2O/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="57ee8123d9c9aefcf23d9c7f6463c158"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mr-6-211-2025-ie00001.svg" width="8pt" height="14pt" src="mr-6-211-2025-ie00001.png"/></svg:svg>glycerol-d8), both for the free complexes and when conjugated to proteins. The impact of temperature, concentration, and field position within the EPR spectrum on Tm was examined. Results indicate that protons within 5 Å of the Gd(III) ion do not contribute to nuclear spin diffusion (NSD), and protein deuteration offers minimal enhancement in Tm. The dominant phase relaxation mechanisms identified at low concentrations were direct spin-lattice relaxation (T1) and transient ZFS (tZFS) fluctuations. Dynamical decoupling (DD) measurements, using the Carr–Purcell sequence with ∼ 140 refocusing pulses, resolved the presence of two populations: one with a long phase relaxation time, Tm,s, and the other with a short one, Tm,f. The dominating mechanism for the slowly relaxing population is direct-T1. Tm,s showed no concentration dependence and was longer by a factor of about 2 than Tm for both complexes. We tentatively assign the increase in Tm,s to full suppression of the residual indirect-T1-induced spectral diffusion and NSD mechanisms. For the fast-relaxing population, Tm,f is shorter for Gd-TPMTA; therefore, we assign it to populations for which the tZFS mechanism dominates. Because of the relatively short T1 and the contribution of the tZFS mechanism, protein deuteration does not significantly affect Tm.